불한번역과 주어 - 박정섭; Bak Jung-sup (언어와 정보 사회, 2018)
The present work is a study of the translation of the subject of sentence from French into Korean. In French, the sentences most often have the informational structure “Topic-Focus”, and the role of Topic is assumed by the subject of the sentence. A small proportion of French sentences are sentences without a visible Topic. In such sentences, the subject is only a participant in the situation or event described by the sentence. In the Korean translation, in general, the Topic subject is marked with NUN and the subject which is not Topic with KA. Analyzing a Korean translation of The little prince by Saint-Exupery, we find that in the Korean translation, 20% of subjects are marked with KA. Then, we show that these Korean sentences mostly represent the French Topic-less sentences, but sometimes they correspond to the French sentences with a Topic subject, for several reasons including the translator’s inattention or error. As the distortion of the informational structure can sometimes lead to a misunderstanding of the author’s intention, attention should be given to this question.